Experimental and simulated study of line-shape models for measuring spectroscopic parameters using the WM-DAS method — Part II: Broadening and narrowing of select near-infrared H2O and CO lines perturbed by Ar, N2 and He. (September 2021) - Li, Jidong; Du, Yanjun; Ding, Yanjun; Peng, Zhimin
Highlights: Absorption line shapes and spectroscopic parameters of the H 2 O transition at 7299.431  cm and the CO transition at 4297.705  cm were measured in perturbers Ar, and He. The nonlinear pressure dependence of the velocity-changing rates and the speed-dependent coefficients with the corresponding ratios were analyzed by both experiments and simulation. The Dicke narrowing and speed dependent effects were analyzed and compared in different binary systems. Abstract: Wavelength modulation-direct absorption spectroscopy (WM-DAS) has been used to measure the absorption line shapes of the H 2 O transition at 7299.431 cm − 1 and the CO transition at 4297.705 cm − 1 perturbed by Ar, N 2 and He. The foreign-gas broadening, narrowing and pressure-shift parameters were determined from various lineshape models at pressures from 1 to 100 kPa. The measured N 2 -broadening coefficients are the largest among the three perturbers and the measured N 2 - and Ar-pressure-shift coefficients are both negative while that for He is positive. The nonlinear pressure dependence of the velocity-changing rates for the Galatry and Rautian profiles and the speed-dependent coefficients for Speed-dependent Voigt profile were all observed for the 6 binary systems. The measured velocity-changing rates were all larger than the corresponding dynamic friction coefficients in H 2 O -Ar/ N 2 /He while smaller than those in CO-Ar/ N 2 /He. The narrowing parameters were also retrieved and compared by taking both the Dicke narrowing and speed dependent effects into account. The partially Correlated quadratic Speed-dependent Hard-Collision profile was simulated and fit by the other simplified profiles to further validate the nonlinear behaviour of the narrowing parameters, which is consistent with the measured results.